Tetrabutylammonium (TBA)-Doped Methylammonium Lead Iodide: High Quality and Stable Perovskite Thin Films - Bouich, Amal; Marí-Guaita, Júlia; Sahraoui, Bouchta; Palacios, Pablo; Marí, Bernabé (Frontiers in Energy Research, 2022)
This work reported the successive incorporation of tetrabutylammonium (TBA) into Methylammonium lead Iodide (MAPbI3) perovskite. The thin films were characterized by X-Ray diffraction (XRD), Scanning electron microscopy (SEM), Transmittance electron microscopy (TEM), Atomic force microscopy (AFM), and UV-Visible spectroscopy. It was shown that introducing TBA increases the crystallinity, grain size, surface morphology without pin-hole, and roughness of the MAPbI3 thin films. Moreover, the MA(1-X)TBAX PbI3 thin film shows better stability in a relative humidity of ∼60% after 15 days than the pure MAPbI3 thin film. The obtained results are hoped to be helpful for stability and improvement of the performance of the MAPbI3 thin films by doping TBA cations under ambient conditions.